Analisis Framing Model Entman pada Pemberitaan Kebocoran Data Aplikasi Pedulilindungi oleh Media Online - Nurhayati, Euis Sri; Laksmi, Laksmi (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2023)
The news media assumes a strategic role in disseminating information. The news media harbors specific objectives when reporting on an event. Lately, the media has extensively covered instances of alleged data leaks from PeduliLindungi app users. This study endeavors to identify the framing employed by online media outlets such as Detik.com, CNNIndonesia.com, and Tribunnews.com in their coverage of the case. The analysis was conducted using Robert N. Entman's framing analysis model. According to the research, the media not only imparts information but also oversees the management of personal data by data controllers and enlightens the public, who are data owners, about personal data protection. The analysis results reveal similarities in the framing of the three online media outlets in terms of (a) problem definition and (b) problem cause. However, there is a distinction between elements (c) determining decisions or moral values and (d) problem-solving. Detik.com and CNNIndonesia.com frame their reporting to provide equal prominence to both data controllers and owners, whereas Tribunnews.com's reporting framework favors data controllers. Based on the research findings, it is plausible to conclude that the framing employed by the three online media outlets is factual.